Reinitiation of chromosome replication in the presence of chloramphenicol under an integratively suppressed state by R6K. - Sotomura, M (1975)
The autonomous replication of an R plasmid, R6K (amp, str) was shown not to be affected by chloramphenicol. It provoked integrative suppression and gave rise to Hfr strains when integrated into the chromosome of a strain of Escherichia coli K-12 with a temperature-sensitive mutation in the gene, dnaA. An Hfr strain designated as Hfr(R6K) no. 1 was thus obtained and characterized. It was not completely stable as shown by a plating efficiency of 0.6 at 42 C relative to that at 30 C. The density labeling and the ultracentrifugation analysis suggested that the deoxyribonucleic acid replication in this Hfr strain did not stop immediately after completion of the round already started before temperature shift-up and the addition of chloramphenicol. These observations are discussed in relation to a possibility that the chromosome replication of this Hfr strain is under the control of the integrated plasmid at a nonpermissive temperature.